A test of the Geographic Mosaic Theory of Coevolution: investigating widespread species of Amazonian Protium (Burseraceae) trees, their chemical defenses, and their associated herbivore faunas - Fine, Paul V. A.; Baccaro, Fabricio Beggiato; Lokvam, John; Mesones, Italo; Vásquez Pilco, Magno; Ayarza Zuñiga, J. Milagros; Merkel, Emerson; Sanches, Marcelle; Nogueira, Carlos A.; Salazar, Diego (Frontiers in Ecology and Evolution, 2023)
Plants and their herbivores represent a large fraction of the species in Amazonian forests and are often directly implicated in the origin and maintenance of biodiversity. How these interactions may change over geographic distance is unknown because very few studies have investigated the herbivore fauna and defense chemicals of any host plant species at multiple sites in tropical forests. One hypothesis, the Geographic Mosaic Theory of Coevolution, predicts that if herbivore assemblages turn over in different parts of a plant's range, then plant defense chemicals should also change, reflecting local selection pressures. We tested this theory by studying 12 species of Protium (Burseraceae) trees that occur in both Iquitos, Peru, and Manaus, Brazil, in rainforests separated by 1500 km. We surveyed all insects feeding at both locations. We analyzed the secondary metabolites of all species using GC/MS and HPLC. Although in both locations we found that Protium herbivores were dominated by insects from the orders Hemiptera, Coleoptera and Lepidoptera, we found almost complete turnover in the herbivore species composition in the two sites. We also found low similarity in herbivore phylogenetic relatedness between host plant species in the two locations. However, the secondary metabolites found within a Protium species were similar across the two locations. We found no strong evidence that individuals from a host plant species in Iquitos or Manaus expressed locally-adapted defense chemicals. These results are not consistent with the Geographic Mosaic Theory of Coevolution. The most intriguing pattern we found was a strong correlation between the diversity of herbivores per host plant species in both locations. We conclude that high chemical diversity is the most effective strategy for Protium trees to reduce insect herbivore attacks. We speculate that each secondary metabolite is effective at repelling only a few insect herbivores, and that different chemicals are likely effective in different parts of a plants' geographic range. Future studies should investigate additional locations and additional natural enemies (i.e., fungal pathogens) to test the hypothesis that chemical diversity reduces attack from natural enemies and may explain the ecological and evolutionary success of rainforest trees over time and space.